A Comparative Study of Requests amongst Second Language Speakers of English - Phindane, Pule (Journal of Sociology and Social Anthropology, 2017)
This paper is based on the findings from a study that investigated the analysis of requests produced by second language (L2) speakers (that is, 15 Afrikaans-speaking (L1) and 17 Sesotho-speaking (L1) learners) of English and how these requests are received by English first language (L1) speakers. The aim of this study is to compare the manners in which Afrikaans first language (L1) and Sesotho first language (L1) speakers make requests when speaking English. The Cross Cultural Speech Act Realization Project (CCSARP) framework of Blum-Kulka was utilized to analyze the requests made by these two groups. The outcomes revealed that Afrikaans speakers used fewer politeness and alert markers as compared to Sesotho speakers who utilized more. The implications of these findings are also discussed.
Published Article
Keywords: Speech Acts; Intercultural; Appropriateness; Communication